Design Improvements in Double-Stator Axial Flux Switched Reluctance Motor for Smoother Torque Profile - Chaudhary K.; Pokhriyal M.; Chaudhary A. (My University, 2025)
—High torque and power generation capability of double-stator axial flux switched reluctance motor (DSAFSRM) makes it superior to conventional and segmented rotor switched reluctance motors. Despite its significant feature, the ripple in developed torque still limits the usefulness of DSAFSRM for widespread industrial application. This paper proposes an 8/6/8 pole DSAFSRM with modification in rotor pole shape to reduce torque ripples in respective model. The respective phase windings of the upper and lower stators are excited externally by preparing the circuit in Maxwell software. Each rotor tooth is constructed with two types of slots with different levels of air gap to change the inductance profile. Firstly, the design of a conventional DSAFSRM has been presented; thereafter, some geometric modifications in the rotor tooth have been suggested and investigated to obtain a lower torque ripple at 1200 rpm in the proposed DSAFSRM. The efficacy of the proposed motor is investigated through finite element method (FEM) based analysis and also by comparative analysis with other types of switched reluctance motors. It can be inferred from the simulation results that the torque ripple is significantly reduced by 55.62% in the proposed DSAFSRM compared to the conventional DSAFSRM. However, the efficiency of the proposed DSAFSRM (73.87%) is slightly less than the conventional DSAFSRM (74.65%). © 2022, Electromagnetics Academy. All rights reserved.